2019
DOI: 10.1038/s41598-019-52222-5
|View full text |Cite
|
Sign up to set email alerts
|

Mapping quantitative trait loci for yield-related traits and predicting candidate genes for grain weight in maize

Abstract: Quantitative trait loci (QTLs) mapped in different genetic populations are of great significance for marker-assisted breeding. In this study, an F2:3 population were developed from the crossing of two maize inbred lines SG-5 and SG-7 and applied to QTL mapping for seven yield-related traits. The seven traits included 100-kernel weight, ear length, ear diameter, cob diameter, kernel row number, ear weight, and grain weight per plant. Based on an ultra-high density linkage map, a total of thirty-three QTLs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Molecular markers are used for the characterization of germplasms, identification and mapping of genes and QTLs for various agriculturally important traits in maize [ 31 , 32 , 33 , 34 , 35 , 36 ]. A previous study identified four simple sequence repeat (SSR) markers linked to the sh2 gene via bulk-segregant analysis (BSA) in three mapping populations [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular markers are used for the characterization of germplasms, identification and mapping of genes and QTLs for various agriculturally important traits in maize [ 31 , 32 , 33 , 34 , 35 , 36 ]. A previous study identified four simple sequence repeat (SSR) markers linked to the sh2 gene via bulk-segregant analysis (BSA) in three mapping populations [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The threshold of corrected P -value 0.005 and log 2 (Fold change) of 1 (absolute value) were considered as significantly differential expression. More information about the methods for reference genome index construction, paired-end clean reads alignment and count, FPKM calculation and DEGs analysis referred to our previous study ( Zhao and Su, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…To date, over 168 primarily mapped QTLs associated with grain size have been reported in sorghum. Among them, 155 QTLs located on ten chromosomes have been mapped for thousand grain weight (TGW) in various independent studies published between 1995 and 2021 [ 13 , 34 , 43 , 45 , 46 , 47 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ] ( Figure 1 a and Table S1 ). Few QTLs related to grain size (21 QTLs for grain length, 23 QTLs for grain width, and 26 QTLs for grain number per panicle) have been identified.…”
Section: Genetic Dissection Of Grain Yield-related Traits In Sorghum ...mentioning
confidence: 99%